Innovative method for incremental dynamic analysis curves in semi-isolated bridges - Hamid Ganjehei; Panam Zarfam; Mohsen Ghafory-Ashtiany (Građevinar)
This paper proposes an innovative method for determining the approximate incremental dynamic analysis curves of semi-isolated bridges, including the derivation of statistical mathematical formulas. Ultimately, an innovative method is devised based on the primary and limit state tangential stiffness values of semi-isolated bridges. The bridges selected for this study are two reinforced concrete highway bridges in the United States, which have been optimally re-designed using lead rubber bearing isolators. The established procedure can be used in future studies to extract the probabilistic responses of semi-isolated bridges via a simplified and efficient method.